SPIRIT GUSJIGANG KUDUS DAN TANTANGAN GLOBALISASI EKONOMI - Mustaqim, Muhamad; Bahruddin, Ahmad (LP2M IAIN kUDUS, 2015)
THE SPIRIT OF GUSJIGANG KUDUS AND THE ECONOMIC GLOBALIZATION CHALLENGES. This paper intends to reveal the role of Gusjigang business spirituality in facing the global economy. Kudus society known to have unique typology in business and learning, it is known as “Gusjigang”, it stands for the good, recite the Qur’an, and trade. Studies on the relationship between spirituality and business have been conducted a lot, but the study of the ethical spirit that focuses on business behavior of Muslim community in the context of the trend of economic globalization would still limited. The unique format and typology resulting from this study is expected to be a new concept for the development of Islamic economics and business at a different time and space in the future. In general, the results of this study came to the conclusion that Gusjigang spirit as glokalitas in business behavior. Glokalitas is a local moral value that is expected to become a universal character. This universal value if applied in the free competition, it will generate business behavior which always brings the perpetrators to goodness.Keywords: Gusjigang, Globalization, Economics.Tulisan ini bermaksud mengungkap peran spiritualitas bisnis Gusjigang dalam menghadapi ekonomi global. Masyarakat Kudus dikenal memiliki tipologi unik dalam berbisnis dan belajar, yang dikenal dengan istilah “Gusjigang”, kepanjangan dari bagus, ngaji, dan dagang. Kajian tentang hubungan antara spiritualitas dan perilaku bisnis memang sudah banyak dilakukan, tetapi kajian tentang spirit etik yang berfokus pada perilaku bisnis masyarakat Muslim konteksnya dengan kecenderungan globalisasi ekonomi kiranya masih terbatas. Format dan tipologi unik yang dihasilkan dari kajian ini diharapkan mampu menjadi konsep baru untuk pengembangan ekonomi dan bisnis Islam pada ruang dan waktu yang berbeda di masa mendatang. Secara umum, hasil kajian ini sampai pada penyimpulan spirit Gusjigang sebagai glokalitas dalam perilaku bisnis. Glokalitas merupakan nilai kearifan lokal yang diharapkan mampu menjadi karakter universal. Nilai universal ini jika diterapkan dalam persaingan bebas, maka akan menghasilkan perilaku bisnis yang senantiasa membawa pelakukunya kepada kebaikan.Kata Kunci: Gusjigang,Globalisasi, Ekonomi.